Venovenous vs. Venoarterial Extracorporeal Membrane Oxygenation in Infection-Associated Severe Pediatric Acute Respiratory Distress Syndrome: A Prospective Multicenter Cohort Study - Cui, Yun; Zhang, Yucai; Dou, Jiaying; Shi, Jingyi; Zhao, Zhe; Zhang, Zhen; Chen, Yingfu; Cheng, Chao; Zhu, Desheng; Quan, Xueli; Zhu, Xuemei; Huang, Wenyan (Frontiers in Pediatrics, 2022)
Background: Extracorporeal membrane oxygenation (ECMO) has been increasingly used as rescue therapy for severe pediatric acute respiratory distress syndrome (PARDS) over the past decade. However, a contemporary comparison of venovenous (VV) and venoarterial (VA) ECMO in PARDS has yet to be well described. Therefore, the objective of our study was to assess the difference between VV and VA ECMO in efficacy and safety for infection-associated severe PARDS patients. Methods: This prospective multicenter cohort study included patients with infection-associated severe PARDS who received VV or VA ECMO in pediatric intensive care units (PICUs) of eight university hospitals in China between December 2018 to June 2021. The primary outcome was in-hospital mortality. Secondary outcomes included ECMO weaning rate, duration of ECMO and mechanical ventilation (MV), ECMO-related complications, and hospitalization costs. Results: A total of 94 patients with 26 (27.66%) VV ECMO and 68 (72.34%) VA ECMO were enrolled. Compared to the VA ECMO patients, VV ECMO patients displayed a significantly lower in-hospital mortality (47% vs. 26.92%, p=0.044) and proportion of neurologic complications, shorter duration of ECMO and MV, but the rate of successfully weaned from ECMO, bleeding, bloodstream infection complications and pump failure were similar. By contrast, oxygenator failure was more frequent in patients receiving VV ECMO. No significant intergroup difference was observed for the hospitalization costs. Conclusion: These positive findings showed the conferred survival advantage and safety of VV ECMO compared with VA ECMO, suggesting that VV ECMO may be an effective initial treatment for patients with infection-associated severe PARDS.